FAKTOR-FAKTOR YANG MEMPENGARUHI KENYAMANAN PETUGAS KESEHATAN DI PUSKESMAS TERPENCIL KECAMATAN TEUPAH SELATAN KABUPATEN SIMEULUE TAHUN 2017 - irmansyah Irmansyah (Universitas Prima Indonesia, 2018)
Regency Simeulue Subdistrict Teupah Selatan health centers in Many health workers who are uncomfortable working at Teupah Seulatan Community Health Center because of the availability of facilities that are less complete, can not develop careers and incentives are lacking. The purpose of this study is to determine the Factors that Affect the comfort of health workers In Clinics Remote Subdistrict Teupah Selatan Regency of Simeulue 2017. This study is held from from March 05th to 29thApril 2017, This research is descriptive analytic with cross sectional approach. The subject is the entire health workers. Total sample of 68 health workers by total sampling. Data were analyzed using Chi-square test statistic. The results showed that there is a meaningful relationship between the incentives with the convenience of a health worker with the value p 0.011 (p < 0.05), there is a meaningful relationship between the availability of the facilities with the convenience of a health worker with a value of 0.001 p (p < 0.05), there is a very meaningful relationships between career development with the convenience of a health worker with the p value of 0.005 (p < 0.05), and there is a very meaningful relationship between the additional income with the convenience of a health worker with a value of 0.012 p (p < 0.05). Conclusions can be taken and additional income that incentives, availability of facilities, career development, connect meaningfully with the convenience of health workers in Clinics Remote Subdistrict Teupah Selatan Regency of Simeulue 2017